2014
DOI: 10.1186/2193-1801-3-315
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of antioxidant activities of extracts from 19 Chinese edible flowers

Abstract: Extracts of 19 selected edible flowers were investigated for their free radical scavenging activity (FRSA), polyphenolic contents and flavonoid contents in the paper. The results showed the extracts of Paeonia suffruticosa Andr., Paeonia lactiflora Pall., and Rosa rugosa Thunb. possessed obviously stronger DPPH FRSA (94.221 ± 0.102; 93.739 ± 0.424 and 94.244 ± 0.163%, respectively), superoxide FRSA (55.818 ± 1.518; 52.142 ± 1.374 and 57.321 ± 0.608%, respectively), hydroxyl FRSA (85.872 ± 0.873; 89.307 ± 0.803… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
40
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 29 publications
9
40
0
1
Order By: Relevance
“…[24] As shown in Table 2, four Rosa species detected in the experiment including rose (312.21 mg GAE/g), French rose (111.34 mg GAE/g), Yunnan rose (108.94 mg GAE/g), and China rose (284.80 mg GAE/g), are found to have relatively higher TPC value compare to the rest of the samples. Previous studies [4,20,25] have also reported that Rosa species contained high amounts of phenolic compounds, and thus exhibits high TPC values. Zeng et al [20] reported that rose flower contains high amount TPC (92.16 mg CE/g).…”
Section: Phenolics In Edible Flowersmentioning
confidence: 87%
See 3 more Smart Citations
“…[24] As shown in Table 2, four Rosa species detected in the experiment including rose (312.21 mg GAE/g), French rose (111.34 mg GAE/g), Yunnan rose (108.94 mg GAE/g), and China rose (284.80 mg GAE/g), are found to have relatively higher TPC value compare to the rest of the samples. Previous studies [4,20,25] have also reported that Rosa species contained high amounts of phenolic compounds, and thus exhibits high TPC values. Zeng et al [20] reported that rose flower contains high amount TPC (92.16 mg CE/g).…”
Section: Phenolics In Edible Flowersmentioning
confidence: 87%
“…Previous studies [4,20,25] have also reported that Rosa species contained high amounts of phenolic compounds, and thus exhibits high TPC values. Zeng et al [20] reported that rose flower contains high amount TPC (92.16 mg CE/g). Whereas, Li et al [4] reported significant TPC in case of China rose (35.84 mg GAE/g wet basis); and another study by Xiong et al [25] reported that China rose and rose high TPC contents 205.5 mg CE/g dry basis and 116.6 mg CE/g dry basis, respectively.…”
Section: Phenolics In Edible Flowersmentioning
confidence: 87%
See 2 more Smart Citations
“…Ethanol extracts of OF fl ower (EOF) were shown to be characterized by a high content of total phenolics (TPC) and a strong antioxidant activity [Ouyang et al, 2015;Wu et al, 2009;Lee et al, 2007;Huang et al, 2015]. The phenolic extracts of OF exhibited evident augments in ferric reducing antioxidant power assay (FRAP) and radical scavenging ability in vitro [Wu et al, 2009; Lee et al, 2007;Zeng et al, 2014]. The extracts also inhibited lipid per-oxidation initiated by ferrous chloride in rat brain, liver, heart and kidney mitochondria [Lee et al, 2007], and the growth of P. gingivalis, especially in iron-limited culture medium, and markedly upregulated the expression of the cytoprotective enzyme and nucleoprotein Nrf2 [Huang et al, 2015].…”
Section: Introductionmentioning
confidence: 99%